Analysis of Financial Feasibility and Business Economics Manalagi Mango Cultivation: (Case Study in Mertani Village, Karanggeneng District, Lamongan Regency) - Hamidah, Emmy (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
The assessment of the feasibility of Manalagi Mango cultivation in Mertani Village, Karanggeneng District, Lamongan Regency, and the analysis of the sensitivity of this cultivation to increased production costs, decreased production, and reduced output prices are the main objectives of this study. The study was conducted in Mertani Village, Karanggeneng District, Lamongan Regency, using a census approach encompassing all populations as respondents. Both primary and secondary data were employed, with data analysis involving quantitative metrics and sensitivity rate analysis using a 15% discount factor. Qualitative descriptive analysis was utilized to evaluate technical cultivation aspects and market factors. Data collection occurred in March 2021. The findings revealed that intensive Manalagi Mango cultivation in the area was financially feasible, with a Gross Benefit Cost Ratio of 4.7, Net Benefit Cost Ratio of 9.94, NPV of IDR 278,880,609, and an IRR of 35%. Additionally, the study demonstrated the resilience of mango cultivation to potential challenges, including a 10% increase in production costs, a 25% decrease in production, or a 10% reduction in output prices, highlighting its feasibility and profitability. The study also noted the favorable climate and rainfall conditions for Manalagi mangoes, though technological adoption among farmers remained limited. Despite variances in sales compared to other crops, the mango cultivation business in Mertani Village remains promising.